Re-Imaging the Role of Clinical Training for Hospital Chaplaincy and Pastoral Care: Moving Beyond Institutional Walls to the Community - Gaventa, William C. (Journal of religion in disability & rehabilitation, 1996)
The author envisions the emerging community roles of chaplains and pastoral caregivers in the ever-changing health care system of the United States. Particular attention is given to ministry with persons who have disabilities.